Inspiring Leadership and Its Role in Boosting Organizational Quality Analytic Study at the Iraqi Islamic Bank for Investment and Development - Mohammed Thaer Ali ALBayati (Indonesian Journal of Law and Economics Review, 2026)
General Background: Leadership plays a critical role in organizational performance and the ability of institutions to adapt to dynamic environments. Specific Background: Inspiring leadership, characterized by future vision, self-confidence, change management, and employee empowerment, is increasingly associated with the development of organizational quality. Knowledge Gap: However, empirical evidence explaining how these leadership dimensions relate to organizational quality in Islamic banking institutions remains limited. Aims: This study analyzes the relationship between inspiring leadership and organizational quality at the Iraqi Islamic Bank for Investment and Development. Results: Using data from 279 employees and applying descriptive statistics, simple linear regression, and stepwise regression, the findings reveal a significant positive relationship between inspiring leadership and organizational quality, explaining about 53.1% of its variance. Self-confidence, future vision, and change management emerge as the most prominent determinants, while employee empowerment shows limited statistical contribution. Novelty: The study provides empirical evidence regarding the relative importance of inspiring leadership dimensions in explaining organizational quality within an Islamic banking context. Implications: The findings suggest that strengthening leaders’ confidence, clarifying future vision, and improving change management practices can support the development of organizational quality in banking institutions. Highlights:  • Leadership Self-Confidence Emerges as the Strongest Determinant of Institutional Quality Variation.• Strategic Vision and Structured Change Practices Jointly Strengthen Internal Performance Conditions.• Staff Autonomy Mechanisms Show Limited Statistical Contribution Within the Examined Banking Context. Keywords: Inspiring Leadership, Organizational Quality, Islamic Banking, Leadership Self-Confidence, Change Management.